2022
DOI: 10.1080/17460441.2022.2029843
|View full text |Cite
|
Sign up to set email alerts
|

The discovery and development of transmembrane serine protease 2 (TMPRSS2) inhibitors as candidate drugs for the treatment of COVID-19

Abstract: Introduction Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has caused the devastating pandemic named coronavirus disease 2019 (COVID-19). Unfortunately, the discovery of antiviral agents to combat COVID-19 is still an unmet need. Transmembrane serine protease 2 (TMPRSS2) is an important mediator in viral infection and thus, TMPRRS2 inhibitors may be attractive agents for COVID-19 treatment. Areas covered This review article discusses the role of TMPRSS2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 100 publications
(116 reference statements)
0
16
0
Order By: Relevance
“…On one hand, testosterone inhibits the release of pro-inflammatory cytokines, modulates the immune response, and attenuates oxidative stress and endothelial dysfunction. On the other hand, high testosterone levels might increase susceptibility and severity of COVID-19 through augmentation of TMPRSS2, which is crucial for cleaving and activation of SARS-CoV-2 spike protein during acute SARS-CoV-2 infection [63].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, testosterone inhibits the release of pro-inflammatory cytokines, modulates the immune response, and attenuates oxidative stress and endothelial dysfunction. On the other hand, high testosterone levels might increase susceptibility and severity of COVID-19 through augmentation of TMPRSS2, which is crucial for cleaving and activation of SARS-CoV-2 spike protein during acute SARS-CoV-2 infection [63].…”
Section: Discussionmentioning
confidence: 99%
“…The structure of TMPRSS2 is characterized by an N-terminal cytoplasmic domain, a transmembrane domain, a class A LDL receptor domain, a scavenger receptor cysteine-rich domain, and an activation domain linked to a serine protease domain via a disulfide bond. 54 , 159 , 170 Since no crystal structure of TMPRSS2 is available, repurposing or optimizing inhibitors against well-known serine proteases may facilitate the discovery of effective TMPRSS2 inhibitors against SARS-CoV-2. 170 – 172 For example, Sun et al identified structurally similar serine proteases using a structure-based phylogenetic computational tool to find potential inhibitors of TMPRSS2.…”
Section: Covid-19 Therapeutic Targets For Small Moleculesmentioning
confidence: 99%
“… 54 , 159 , 170 Since no crystal structure of TMPRSS2 is available, repurposing or optimizing inhibitors against well-known serine proteases may facilitate the discovery of effective TMPRSS2 inhibitors against SARS-CoV-2. 170 – 172 For example, Sun et al identified structurally similar serine proteases using a structure-based phylogenetic computational tool to find potential inhibitors of TMPRSS2. 173 According to their computational results, six serine peptidases, including kallikrein-related B1, had a high structural similarity to the TMPRSS2 S1 protease domain.…”
Section: Covid-19 Therapeutic Targets For Small Moleculesmentioning
confidence: 99%
“…It has been suggested that another TMPRSS2 inhibitor, bromhexine, presently used as a mucolytic cough suppressant, could be used to treat COVID-19 ( Habtemariam et al, 2020 ; Maggio and Corsini, 2020 ). Novel TMPRSS2 inhibitors have recently been identified using high-throughput screening ( Mantzourani et al, 2022 ), and a highly potent inhibitor has recently been well characterized ( Shapira et al, 2022 ). This compound, N-0385, is a small peptidomimetic that is active at low doses (nanomolar) and inhibits SARS-CoV-2 infection in human lung cells and in donor-derived colon organoids.…”
Section: Drugs and Neutralizing Monoclonal Antibodies Preventing Sars...mentioning
confidence: 99%